2008
DOI: 10.1002/em.20367
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory activity of a Lactobacillus casei strain on 1,2‐dimethylhydrazine‐induced genotoxicity in rats

Abstract: The present study was designed to investigate the putative antigenotoxic effects of supplementing the diet of rats treated with the colon carcinogen 1,2-dimethylhydrazine hydrochloride (DMH) with a Lactobacillus casei strain using an in vivo approach. The antigenotoxic response was evaluated in colon and liver cells using the alkaline comet assay. Since the balance between the bioactivation and detoxification metabolic pathways is crucial for the formation of toxic and genotoxic metabolites, alterations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…PhIP did not show any genotoxic effect in liver cells and, consequently, it was not possible to evaluate potential antigenotoxic properties of the tested Lactobacillus rhamnosus strain in this organ. The beneficial effects reported in the present paper for the challenge lactobacilli/ PhIP are in agreement with previous reports indicating that oral administration of probiotics effectively reduces the extent of induced DNA damage in model animals [12,33,49,54].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…PhIP did not show any genotoxic effect in liver cells and, consequently, it was not possible to evaluate potential antigenotoxic properties of the tested Lactobacillus rhamnosus strain in this organ. The beneficial effects reported in the present paper for the challenge lactobacilli/ PhIP are in agreement with previous reports indicating that oral administration of probiotics effectively reduces the extent of induced DNA damage in model animals [12,33,49,54].…”
Section: Discussionsupporting
confidence: 93%
“…The results of our previous studies have demonstrated the ability of lactobacilli, bacilli, and yeasts to counteract in vitro various food mutagens, among which include 4-nitroquinoline-N-oxide, N-methyl-N'-nitro-N-nitrosoguanidine, heterocyclic amines, and aflatoxin B 1 [4,8,51]. Carcinogenesis studies conducted in laboratory animals have shown that some probiotics (i.e., lactobacilli and bifidobacteria) seem capable of counteracting the DNA damage activity exerted by potent food mutagens (2amino-3-methylimidazo[4,5-f]quinoline, DMH, aflatoxin B 1 , azoxymethane) with consequent reduction of a pre-neoplastic state and protection against tumors induced by these compounds [19,26,39,54]. For these reasons, every strategy reducing mutagen presence may be effective in carcinogenesis prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The lacto-ovo-vegetarian habit, a less restrictive dietary pattern than the vegan one, was particularly effective in lowering the levels of both FW genotoxicity and cytotoxicity. This finding highlights the possible contribution of this dietary habit in reducing the risk of carcinogenesis at intestinal level and is consistent with our previous studies concerning the antigenotoxic activity of some probiotics and food-borne microorganisms in animal models ( Villarini et al, 2008 ; Dominici et al, 2014 ). Indeed, the capacity of food-borne bacteria and yeasts with acid-bile resistance to significantly reduce the activity of model genotoxins, such as nitroarenes, alkylating agents, mycotoxins, and heterocyclic amines, has been already demonstrated in vitro ( Caldini et al, 2005 ; Cenci et al, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…The diet-related metabolomic features of the digestive tract may endogenously affect the induced expression of fecal microbial enzymes (β-glucuronidase, nitroreductase, azoreductase, 7-α-dehydroxylase) involved in the metabolic activation of pre-carcinogen, and the activity of mucolytic enzymes (β-glucosidase, N -acetyl-β- D -glucosaminidase) that increase colonocyte susceptibility to genotoxic compounds ( Cenci et al, 1993 ; Fotiadis et al, 2008 ; Villarini et al, 2008 ). Furthermore, even secondary bile acids, nitrosamines and fecapentaenes originated by microbial metabolism have genotoxic properties ( de Kok and van Maanen, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1415] Probiotic-containing foods have been reported to suppress oxidative stress. It has been shown that Lactobacillus casei decreased the oxidative stress[16] and suppressed the effector functions of CD4 + T-cells, accompanied by reducing the proinflammatory molecules,[17] thus having antioxidant and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%